The Effect Of Brand Image, Digital Marketing, Product Quality And Price On Purchasing Decisions Of Indomie Products - Stiawan, Erix; Ariska, Yesi Indian; Zoniarti, Zoniarti (Journal of Management, Economic, and Accounting, 2025)
Indomie continues to adapt trends and consumer preferences by launching product variants that suit local tastes or follow certain food trends to help Indomie remain relevant in the market. The purpose of this study is to determine the effect of brand image, digital marketing, product quality and price on purchasing decisions of Indomie products. This type of research is quantitative. The data collection method in this study used a questionnaire technique, with a sample of 125 respondents. The results showed that multiple linear regression Y = 0.246 + 0.351 X1 + 0.114 X2 + 0.457 X3 + 0.072 X4 + 0.193. Where the coefficient is positive, it means that there is a positive or unidirectional relationship between the brand image variable (X1), digital marketing (X2) product quality (X3), price (X4), the value is 0 (zero), on purchasing decisions (Y) indomie products. The results showed that the brand image test (XI) showed a t count of 8,248> t table 1,657 and a sigfinication of 0.000<0.05, so the results of Ha are accepted and Ho is rejected, meaning that brand image has a positive and significant effect on purchasing decisions of indomie products. The digital marketing test results (X2) show t count 3.652> t table 1.657 and sigfinication 0.000 <0.05, then the results of Ha are accepted and Ho is rejected, meaning that digital marketing has a positive and significant effect on purchasing decisions of indomie products. The results of the product quality test (X3) show t count 10.060> t table 1.657 and sigfinication 0.000 <0.05, then the results of Ha are accepted and Ho is rejected, meaning that product quality has a positive and significant effect on purchasing decisions of indomie products. The price test results (X4) show t count 2.550> t table 1.657 and sigfinication 0.012<0.05, then the results of Ha are accepted and Ho is rejected, meaning that price has a positive and significant effect on purchasing decisions of indomie products. Based on the comparison of Fcount with Ftable, the value of Fcount is greater than Ftable, namely 13,136>2.29, it is concluded that it accepts the hypothesis, meaning that there is a simultaneous influence between brand image (X1), digital marketing (X2) product quality (X3), price (X4) on purchasing decisions (Y) indomie products. This can be seen at a significance level of 0.000 <0.05